Aggregation‐Induced Emission in a Flexible Phosphine Oxide and its Zn(II) Complexes—A Simple Approach to Blue Luminescent Materials. (24th January 2023) - Kirst, Christin; Knechtel, Fabian; Gensler, Manuel; Fischermeier, David; Petersen, Jens; Danaf, Nader A.; Tietze, Jonathan; Wedel, Armin; Lamb, Don C.; Mitrić, Roland; Karaghiosoff, Konstantin
Abstract: Easily accessible blue‐emitting materials are in the focus of ongoing research, as they still lack the efficiency and lifetime of their red and green counterparts. The new multidentate phosphine oxide ligands and two respective ZnCl2 complexes presented here combine a straightforward synthesis with high yields and show interesting luminescent properties. The free ligand exhibits blue luminescence in the crystalline state, but not in amorphous films or diluted solution. In contrast, the Zn(II) complexes shows intense blue luminescence in the crystalline state as well as in amorphous thin films and in solution. Fluorescence lifetime imaging microscopy measurements show luminescence lifetimes of 3–6 ns indicative of fluorescence. By combining the experimental data with quantum chemical calculations,  we propose a model where the conformation of the molecule is restricted, either via the crystal environment, aggregation, or the steric fixation by the coordinating central atom, blocking the nonradiative relaxation from the excited into the ground electronic state. However, this nonradiative relaxation is still possible in the gas phase via elongation of a PC bond. These results may provide a general mechanism to explain the luminescence properties in a whole class of organic phosphine oxides. Abstract : Aggregation induced emission in a flexible phosphine oxide and its Zn(II) complexes—a simple approach to blue luminescent materials.